2021
DOI: 10.3390/su13137186
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Multi-Criteria Decision Making Model for Defect-Based Condition Assessment of Railway Infrastructure

Abstract: The condition of railway infrastructure, such as rails, ballasts and sleepers, should always be monitored and analyzed to ensure ride safety and quality for both passengers and freight. It is hard to assess the condition of railway infrastructure due to the existence of various components. The existing condition assessment models are mostly limited to only assess track geometry conditions and structural condition of the railway infrastructure. Therefore, the present research develops a defect-based structural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…AFE, namely defect severity ranking, proves less researched. Contrary to our initial expectations of exclusively dictionary-based schemes, of studies found, most now adopt contextual evaluation via fuzzy logic devices [221,222] and probabilistic analysis [33,223]. We infer more complex evaluation grounds are being considered in parallel when grading repair urgency, if not yet for RTSSI.…”
Section: Automated Feature Detection and Evaluationmentioning
confidence: 68%
“…AFE, namely defect severity ranking, proves less researched. Contrary to our initial expectations of exclusively dictionary-based schemes, of studies found, most now adopt contextual evaluation via fuzzy logic devices [221,222] and probabilistic analysis [33,223]. We infer more complex evaluation grounds are being considered in parallel when grading repair urgency, if not yet for RTSSI.…”
Section: Automated Feature Detection and Evaluationmentioning
confidence: 68%
“…The first is the train blockage area, with high ventilation velocity; the second is the At different longitudinal ventilation velocities, the smoke back-layering length will be different for the same heat release rate. When the longitudinal ventilation velocity is lower than the critical ventilation velocity, smoke back-layering will occur, which can be divided into two cases due to the influence of the long metro train [24,25]: (1) smoke is restricted to the length of the metro train; (2) smoke spread exceeds the length of the metro train, as shown in Figure 2.…”
Section: Smoke Spread Exceeds the Length Of The Metro Trainmentioning
confidence: 99%
“…As part of city infrastructure, a rail transit system play a pivotal role in transportation [1]. The development of the metro has greatly facilitated the travel of people, but it has also brought many safety problems.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies aimed at exploiting the use of multi-criteria decision making algorithms for assessing the condition of infrastructure systems. (El-khateeb et al, 2021) analyzed the performance condition of railway infrastructure using a defect-based model. The overall condition was obtained based on rails, sleeper, track geometry, ballast and insulated rail joints.…”
Section: Previous Research Studiesmentioning
confidence: 99%